(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
Optimum conditions of the bismuth(III) sorption on the silica gels, chemically modified by mercaptopropyl groups (MPS), are established. The sorption activity of MPS in optimal conditions in relation to bismuth(III) depending on the degree of surface filling by grafted groups and on the geometric parameters of matrix was researched. It was established, that, independently of a concentration of grafted groups on the surface of MPS, complexes with composition Bi:SH 1:2 are mostly formed. It is shown, that MPS can be used for sorption-photometric determination of bismuth. Upon the treatment of the sorbate by thiourea solution the level of photometric determination of bismuth in the sorbent phase is 1 μkg/0,1 g of the MPS.